The Deconstruction of Modern Mortality of Death: An Analysis Through Law, War, and Social Philosophy - Tomasz Wierzchowski; Bożena Iwanowska; Dawid Stadniczeńko; Yan Kapranov (Journal of Modern Science)
Objectives This paper aims to explore the deconstruction of contemporary mortality through a multidisciplinary approach, focusing on law, warfare, and social philosophy. It examines how modern society navigates the complexities of death, both legally and socially, and investigates the impact of warfare and aging on perceptions of mortality.